Chamilo LMS Research Trend: A Systematic Literature Review - Nasrum, Akbar; Nasir, Agus (International Journal of Business, Law, and Education, 2023)
Chamilo is an open-source Learning Management System that is rarely known by campus communities in Indonesia, even though this LMS has been published for quite some time. Very little research is related to Chamilo compared to other LMS such as Moodle. This study will examine research trends over the past ten years using the Systematic Literature Review method. The subjects studied were taken from the Dimension and Scopus databases. The tools used are VoS Viewer and Mendeley software. The unit of analysis used is the "co-author," which is studied deductively. In addition, the type of "co-occurrence" is also used to see the keywords that are most often used in research. The research results showed that 69% of all articles were from Indonesia. The type of development research also dominates articles originating from Indonesia. The most dominant keyword besides Chamilo itself is e-learning. Several research keywords that are not included in the occurrence analysis unit have the potential to be studied.